PLAGL2 as a prognostic biomarker and an EMT-promoting factor in PDAC - Yan-Hui Yang; Hao Wang; Zhe-Hua Xing; Qian-Qian Bai; Wei-Feng Liu; Da-Huan Li; Chi Zhang; Shu-Min Zhang; Fang-Fei Liu; Yu-Bo Liu; Hua Fan (Scientific Reports)
Abstract Pancreatic ductal adenocarcinoma (PDAC), the most prevalent form of pancreatic malignancy, is characterized by its aggressive nature and high mortality rate, with a 5-year survival rate in China of only 9.9%. Polymorphic adenoma gene-like 2 (PLAGL2) has been implicated in the development of various digestive tract tumors, including hepatocellular carcinoma, gastric carcinoma, and colorectal carcinoma, and it influences tumor progression through multiple pathways. However, the specific role and mechanism of PLAGL2 in PDAC requires further investigation. The objective of this study was to evaluate the expression level of PLAGL2 in PDAC and its association with clinical parameters, thereby assessing its prognostic significance for PDAC, and its impact on the malignant process. We first analyzed the expression of PLAGL2 in pancreatic ductal adenocarcinoma (PDAC) via multiple databases, including TCGA and GTEx, to investigate its associated enrichment pathways. We subsequently examined the expression of PLAGL2 via immunohistochemistry and PCR in PDAC tumor tissue samples from our hospital, explored the relationships between PLAGL2 expression and clinical features, and evaluated the predictive value of PLAGL2 for the survival of PDAC patients. we investigated the effect of PLAGL2 on the epithelial‒mesenchymal transition (EMT) process by examining its association with the expression of EMT-related proteins. Finally, We confirmed that PLAGL2 facilitates the proliferation, invasion, and migration of PDAC using conventional cellular assays. The immunohistochemistry and PCR results, combined with the results of GEPIA analysis, indicated that PLAGL2 was significantly overexpressed in patients with pancreatic ductal adenocarcinoma (PDAC). GO analysis revealed that PLAGL2 was intricately linked to protein modification and regulation, as well as nerve projection development. The KEGG and GSEA enrichment analyses indicated that several signaling pathways, including the PI3K-AKT pathway, were significantly enriched, particularly in relation to EMT. The characterization of PLAGL2 expression and its clinicopathological features indicated that high PLAGL2 expression was associated with poor prognosis in PDAC patients and was positively correlated with TNM stge, TNM: T,TNM: N, Tumor size, Nerve infiltration and other clinical characteristics of the tumor. Immunohistochemical analysis suggested that PLAGL2 plays a role in enhancing the epithelial-to-mesenchymal transition (EMT) process in PDAC. By knocking down or overexpressing PLAGL2 in PDAC cell lines and conducting a series of cellular experiments, we ultimately demonstrated that low expression of PLAGL2 inhibits proliferation, migration, and invasion in PDAC, while high expression of PLAGL2 promotes these processes. This study demonstrated that the expression level of PLAGL2 serves as a predictive biomarker for survival in patients with pancreatic ductal adenocarcinoma (PDAC). It is associated with clinical features, including TNM stge, Tumor size, Nerve infiltration, and it also plays a role in promoting epithelial‒mesenchymal transition (EMT) in PDAC, and promotes the proliferation, migration and invasion of PDAC.